A Case Study On Self-Regulation In Early Childhood With Intellectual Developmental Delay - Nurachmi Maisyaroh; Brigita Puridawaty; Nadia Masfhufaturahmah; Teta Nurul Ismah; Eka Safrianti; Ida Nuraida (Journal of Scientific Research, Education, and Technology (JSRET), 2026)
Self-regulation is a crucial ability in early childhood development, encompassing the control of attention, behavior, and emotions within learning contexts and social interactions. This ability serves as a foundational component of children’s learning readiness and social adjustment in educational settings. Children with intellectual developmental delay often experience difficulties in self-regulation due to limitations in cognitive capacity and executive functioning, which subsequently affect learning engagement and social adaptability. This study aimed to describe the self-regulation of an early childhood learner with intellectual developmental delay using a case study approach. The research employed a descriptive qualitative method with continuous observation conducted over a four-month period in a kindergarten learning environment. The research subject was a six-year-old child diagnosed with moderate intellectual developmental delay. Observations focused on attention regulation, behavioral regulation, emotional regulation, and social-emotional functioning during learning activities. The findings revealed that the child’s self-regulation had not developed in accordance with chronological age expectations. The most prominent difficulties included limited sustained attention, dependence on external guidance for behavior regulation, emotional instability when facing challenges, and restricted peer interactions. These findings indicate that intellectual developmental delay affects multiple and interrelated aspects of self-regulation, highlighting the importance of understanding self-regulation based on developmental rather than chronological age